2022
DOI: 10.1093/pcp/pcac120
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal Development and Gene Expression in Rice Florets

Abstract: Stomata play a fundamental role modulating the exchange of gases between plants and the atmosphere. These microscopic structures form in high numbers on the leaf epidermis and are also present on flowers. Although leaf stomata are well-studied, little attention has been paid to the development or function of floral stomata. Here, we characterise in detail the spatial distribution and development of the floral stomata of the indica rice variety IR64. We show that stomatal complexes are present at low density on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…To see if leaves with increased stomatal conductance also displayed a mesophyll phenotype, two transgenic rice lines overexpressing EPFL9 were used: OsEPFL9OE-2 and OsEPFL9OE-3 (Bertolino et al ., 2022). Compared to IR64, these lines had a significantly higher stomatal conductance ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To see if leaves with increased stomatal conductance also displayed a mesophyll phenotype, two transgenic rice lines overexpressing EPFL9 were used: OsEPFL9OE-2 and OsEPFL9OE-3 (Bertolino et al ., 2022). Compared to IR64, these lines had a significantly higher stomatal conductance ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, manipulating SD (e.g. Bertolino et al, 2022) or function (Lawson & Matthews, 2020) in wheat ears alone could improve heat tolerance and support greater photosynthesis through increased evaporative cooling, influence translocation of photoassimilates and nutrients to the grains and provide a route to improve nonfoliar water-use efficiency. New Phytologist (2023) www.newphytologist.com…”
Section: Role Of Stomata In Nonfoliar Tissuementioning
confidence: 99%
“…3; Hu et al, 2019;Henry et al, 2020;Simkin et al, 2020), and certain fruits (Brazel & Ó'Maoiléidigh, 2019); however, their functionality, including their contribution to carbon acquisition, has not been fully evaluated (Simkin et al, 2020). Recent work by Bertolino et al (2022) has reported considerable spatial variation in stomata in rice floral organs and suggested that they are morphologically distinct from leaf stomata, although their function is still unknown.…”
Section: Role Of Stomata In Nonfoliar Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Transpiration is controlled by several thousand microscopic porous organs called stomata, which are found in all plant leaves and floral parts. These organs are distributed throughout the phyllosphere, including leaf surfaces, leaf sheaths (stems), floral parts and even tiny anthers ( Bertolino et al., 2022 ). Stomatal traits vary between eudicots and monocots.…”
Section: Introductionmentioning
confidence: 99%